Efisiensi Investasi : Pengaruh Pengungkapan Environmetal, Social and Governace (ESG), Debt Maturity dan Kualitas Laporan Keuangan - Ahmad Hafizh Zaky; Erna Hendrawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study analyzes the influence of Environmental, Social, and Governance (ESG), debt maturity, and the quality of financial statements on investment efficiency in 104 samples of LQ45 index companies on the Indonesia Stock Exchange for the 2020–2023 period. Using a quantitative analysis approach with multiple linear regression, the data were processed through IBM SPSS Statistic 23. Simultaneously, the three independent variables affect investment efficiency with a determination coefficient of 12.5%.  The results show that debt maturity and the quality of financial statements have a significant effect on investment efficiency, with debt maturity having a negative effect and the quality of financial statements having a positive effect. In contrast, ESG has no significant effect. These findings emphasize the importance of short-term debt management and financial statement transparency in reducing overinvestment, while ESG disclosures require stronger governance to support investment efficiency.